Implementation of the international plan of action to prevent, deter and eliminate illegal, unreported and unregulated fishing : relationship to, and potential effects on, fisheries management in the Mediterranean (Food and Agirculture Organization of the United Nations, 2005)
This paper sets out the evolving management role of regional fisheries management organizations (RFMOs), as agreed in recent international fisheries instruments. Issues common to illegal, unreported and unregulated (IUU) fishing and management of fishing capacity are described, especially as contained in the International Plans of Action (IPOAs) relating to these areas.